The Development of a Knowledge Sharing Behavior Scale in the Thai Context - Chuymanee, Kotchaworn; Sorod, Bung-on (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 3 (2561): July-September 2018, 2018)
The main purposes of this study were to investigate a construct of integrated knowledge sharing behavior and consequently to develop a valid and reliable instrument to quantify the knowledge sharing behavior of Thai employees. Therefore, the main procedures of this study were establishing a definition of KSB and its elements, developing a preliminary scale, and testing the quality of the scale. Accordingly, 34 KSB items were initially listed. After being reviewed and revised by experts, 2 items were suggested to be deleted. The 32-item KSB scale, then, was used to collect data from 605 hard disk drive employees in four large companies.      Four emerging meaningful constructs of 19-item KSB scale, including explicit knowledge donation, tacit knowledge contribution, reactive knowledge receiving, and proactive knowledge acquiring, were identified by performing an exploratory factor analysis. Consequently, a confirmatory factor analysis was conducted for validating the scale. The results of the adjusted model displayed good fit with the data (χ 2 = 148.67, df = 123, normed chi-square (χ 2 /df) = 1.21, p-value = 0.06, SRMR = 0.04, RMSEA = 0.03, CFI = 0.99, and TLI = 0.99). In addition, the scale was found to be highly reliable (Cronbach’s alpha of the KSB scale was 0.92) and each item possessed high discriminant value. Further studies should focus on finding score ranges for this 19-item KSB scale with other groups of Thai people and should validate the scale with similar behaviors and other variables. Keywords : Knowledge Sharing Behavior, Scale Development, Hard Disk Drive Industry, Thai Context